Crosstalk between acetylation and the tyrosination/detyrosination cycle of α-tubulin in Alzheimer’s disease - Martínez-Hernández, José; Parato, Julie; Sharma, Aditi; Soleilhac, Jean-Marc; Qu, Xiaoyi; Tein, Ellen; Sproul, Andrew; Andrieux, Annie; Goldberg, Yves; Moutin, Marie-Jo; Bartolini, Francesca; Peris, Leticia (Frontiers in Cell and Developmental Biology, 2022)
Microtubules (MTs) support a variety of neuronal functions, such as maintenance of cell structure, transport, and synaptic plasticity. Neuronal MTs are highly heterogeneous due to several tubulin isotypes and the presence of multiple post-translational modifications, such as detyrosination and acetylation. The tubulin tyrosination/detyrosination cycle is a key player in the maintenance of MT dynamics, as tyrosinated tubulin is associated with more dynamic MTs, while detyrosinated tubulin is linked to longer lived, more stable MTs. Dysfunction of tubulin re-tyrosination was recently correlated to Alzheimer’s disease progression. The implication of tubulin acetylation in Alzheimer’s disease has, however, remained controversial. Here, we demonstrate that tubulin acetylation accumulates in post-mortem brain tissues from Alzheimer’s disease patients and human neurons harboring the Alzheimer’s familial APP-V717I mutation. We further show that tubulin re-tyrosination, which is defective in Alzheimer’s disease, can control acetylated tubulin in primary neurons irrespective of the levels of the enzymes regulating tubulin acetylation, suggesting that reduced MT dynamics associated with impaired tubulin re-tyrosination might contribute to the accumulation of tubulin acetylation that we detected in Alzheimer’s disease.